Pengaruh Faktor Keuangan terhadap Cash Holding pada Perusahaan Sektor Pertambangan (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of cash flow, cash conversion cycle, capital expenditure, and net working capital on cash holding in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. This study uses a quantitative approach with multiple linear regression methods. The data used is secondary data obtained from the company's annual financial statements. The results showed that cash flow and cash conversion cycle have a positive and significant effect on cash holding. Conversely, capital expenditure has a negative and significant effect, while net working capital has no significant effect on cash holding. These findings support the trade-off theory in the context of corporate cash management, where companies need to balance between liquidity needs and efficient use of cash. This research is expected to contribute to financial decision making, especially related to cash management strategies in the mining industry.